Urinary fractional excretion of estrogen in women with normal cycles - Rodríguez Gutierrez, Washington (2015)
By using the Brown's procedure the authors have measured the urinary excretion of estrone, estradiol and estriol in a group of 10 normal women. Two peaks of excretion were observed: the first corresponding to ovulation and a second one in the luteal phase; both were significantly different of the values obtained in the first phase of the cycle.